The First Epistle Revealed by the Báb to Mírzá Áqásí - Báb, The (2025)
First of four epistles sent to the Prime Minister of Iran, in which the Báb admonishes Áqásí to renounce worldly ambition and uphold justice.
See other Epistles revealed by the Báb to Mírzá Áqásí: Third and Fourth.
Keywords: Báb, Writings of; Hájí Mírzá Aqasi; Mullá Ḥusayn Bushrú'í